Enrichment strategy and initial characterization of heterodimers enriched from a co-formulated cocktail of therapeutic antibodies against SARS-COV-2 - Sophia Liu; Yuetian Yan; Cody M. Secor; Zachary R. Oberholtzer; Donna J. Skow; Mushhood Sheikh; Youmi Moon; Yue Fu; Cristinel Sandu; Shunhai Wang; Ning Li; Jennifer B. Nguyen; et al. (mAbs)
Co-formulation of multiple drug products is an efficient and convenient approach to simultaneously deliver multiple biotherapeutics with the potentially added benefit of a synergistic therapeutic effect. However, co-formulation also increases the risk of heteromeric interactions, giving rise to unique impurities with unknown efficacy and immunogenicity. Therefore, it is critical to develop methods to evaluate the risk of heteromers as an impurity that could affect potency, efficacy, and/or immunogenicity. The most direct strategy to evaluate antibody heteromers is via specific enrichment. However, the fact that antibody heterodimers generated from the co-formulated cocktail share highly similar molar mass and size properties as homodimers natively present in each individual antibody drug product poses a unique purification challenge. Here, we report the path to successful enrichment of heterodimers from co-formulated REGEN-COVⓇ and discuss its potential impacts on drug quality.